2020
DOI: 10.3846/btp.2020.12313
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionised Technologies for Marketing: Theoretical Review With Focus on Artificial Intelligence

Abstract: Information technology and its implications have shown significant developments in the last decades. The internet revolution and digital marketing have created a shrinking force on mass media advertising. They have formed the backbone of personalisation, marketing automation, neuromarketing, viral marketing, voice recognition, and conversion optimisation, and thus, Artificial Intelligence (AI) has risen as the phenomenon in marketing activities. Theoretical analysis of relevant researches on AI tools and futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…The term ‘mobile marketing’ can be found among the significant keywords of this cluster. It has, indeed, been shown that mobile marketing is a revenue driver used by companies operating in the retail industry as part of their marketing automation strategies (Gwon & Seo, 2021; Nair & Gupta, 2020; Peyravi et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The term ‘mobile marketing’ can be found among the significant keywords of this cluster. It has, indeed, been shown that mobile marketing is a revenue driver used by companies operating in the retail industry as part of their marketing automation strategies (Gwon & Seo, 2021; Nair & Gupta, 2020; Peyravi et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Mobile marketing research and studies are always concerned with carefully addressing trust and privacy issues [2]. This study identified the following emerging issues that should be considered in future studies: artificial intelligence [31], cloud computing [32], mobile channels, Internet of Things (IoT) [33], big data marketing [34] and machine learning in mobile marketing [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Peyravi et.al. [12], provides a theoretical review of revolutionized technologies in marketing, with a focus on AI. The research study offers theoretical insights into how AI is reshaping marketing practices and strategies.…”
Section: Literature Reviewmentioning
confidence: 99%